The Effect of Understanding of Taxation, Training, Mentoring, Supervision, and Sanctions on the Village Treasurer's Compliance with the Use of the Core Tax System - Erna Sari; Husnul Muttaqin (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the effect of taxation understanding, training and mentoring, as well as supervision and sanctions on the compliance of village treasurers in using the Core Tax Administration System in reporting Village Funds taxes in Bengkalis, Bantan, and Siak Kecil subdistricts. Using purposive sampling, this study involved 61 village treasurers as respondents. The data were analyzed using multiple linear regression with the help of SPSS version 29. The results show that tax understanding has a positive and significant effect on the compliance of village treasurers (significance = 0.030 <0.05). Conversely, training and mentoring had a positive but insignificant effect (significance = 0.412), while supervision and sanctions had a negative and insignificant effect (significance = 0.099). Simultaneously, the three variables had no significant effect on compliance (significance 0.084 > 0.05). The model was only able to explain 6.2% of the variation in compliance, with the remainder being influenced by factors outside the model.